Leukemogenic transformation by HOXA cluster genes - Bach, Christian; Buhl, Sebastian; Mueller, Dorothee; Garcia-Cuellar, Maria-Paz; Mäthner, Emanuel; Slany, Robert (Blood, 2010)
HOX homeobox genes are important regulators of normal and malignant hematopoiesis. Abdominal-type HOXA genes like HOXA9 are highly leukemogenic. However, little is known about transformation by anterior HOXA genes. Here we performed a comprehensive assessment of the oncogenic potential of every HOXA gene in primary hematopoietic cells. With exception of HOXA2 and HOXA5, all HOXA genes caused a block or delay of hematopoietic differentiation and cooperated with Meis1. No evidence for the alleged tumor-suppressor function of HOXA5 could be found. Whereas all active HOXA genes immortalized mixed granulocytic/ monocytic populations, HOXA13 preferentially specified monocytoid development. The anterior HOXA genes HOXA1, HOXA4, and HOXA6 transformed cells, generating permanent cell lines, although they did so less potently than HOXA9. Upon transplantation these lines induced myeloproliferation and acute myeloid leukemia in recipient animals. Kinetic studies with inducible HOX derivatives demonstrated that anterior HOXA genes autonomously contributed to cellular transformation. This function was not mediated by endogenous Hoxa9, which was persistently expressed in cells transformed by anterior HOX genes. In summary our results demonstrate a hitherto unexpected role of anterior HOXA genes in hematopoietic malignancy. © 2010 by The American Society of Hematology.